التأدب اللغوي في فيلم بلال سلالة بطل جديد (Bilal A New Bread of Hero) المدبلج للعربية (دراسة تحليلية تداولية) - ابن حافظ الفريش (Prosiding Konferensi Nasional Bahasa Arab, 2020)
التأدب اللغوي طريقة التخاطب بين المتكلم و المستمع بالآداب في اللغة. و الغرض من التأدب اللغوي تأسيس شعور جيد و تقليل الحرج للمستمع. هدفت الدراسة الحالية إلى معرفة مدى تحقيق فيلم بلال سلالة بطل جديد لمبادئ التأدب الستة عند جيفري ليتش - مبدأ اللباقة، مبدأ الكرم، مبدأ الاستحسان، مبدأ التواضع، مبدأ الاتفاق، مبدأ التعاطف – كفيلم كرتون الانيميشن الإسلامي المدبلج للغة العربية. أجريت الدراسة على المنهج الكيفي الوصفي بأداة دليل المراقبة أو الملاحظة للمحاورات في الفيلم. و مصدر البيانات فيديو الفيلم نفسه. استنتجت الدراسة أن مبادئ التأدب الستة منفذة جميعا في الفيلم. و كان مبدأ الاستحسان هو أكثر تنفيذا. وبلال كالممثل الرئيسي ينفذ المبادئ غاليا.كلمات المفتاح : التأدب اللغوي، مبادئ التأدب، فيلم كرتون الانيميشن. Linguistic politeness is the method of communication between the speaker and the listener in literature. The purpose of linguistic politeness is to establish a good feeling and reduce the listener's embarrassment. The current study was aimed at knowing the extent to which the film Bilal A New Breed of Hero, achieved the six principles of politeness at Jeffrey Leach - maxim of tact, maxim of generosity, maxim of approbation, maxim of modesty, maxim of agreement and maxim of sympathy - such as the Islamic cartoon film animated and dubbed for the Arabic language. The study was conducted on a descriptive cualitative method, with observation guide tools for the utterances in the film. And the data source is the film video itself. The study concluded that the six principles of politeness are all implemented in the film and maxim of approbation was more implemented. Bilal as the main actor executes principles dearly.Key Words: Linguictic Politeness, Principles of Politeness, Cartoon Film